Nutritional, Sensory and Caking Characteristics of Tatale Mix: A Plantain-Based Convenient Food: Tatale mix: a plantain convenient food product (Journal of Science and Technology, 2025)
Tatale is a popular Ghanaian traditional fried pancake that is prepared from pulped ripe plantain fruit (Musa paradisiaca), cereal flour and spices. In view of the seasonality and perishability of plantain in Ghana, the study was conducted to develop a nutritious, sensory acceptable and free-flowing (shelf-stable) plantain-based convenient food, Tatale mix, that could conveniently be reconstituted for the preparation of Tatale or Kaklo (deep-fried pulped plantain). The nutritional and sensory quality characteristics, and caking behaviour of the experimental Tatale mix were evaluated. The study revealed that the quantities of most nutrients in ripe plantain were similar to those found in the experimental Tatale mix but protein and fibre contents were significantly higher in the Tatale mix developed. The sensory characteristics of the three experimental Tatale mixes were highly acceptable to trained sensory panellists. Experimental Tatale mix prepared with wheat flour was adjudged the best nutritionally with excellent sensory attributes. The study also revealed that calcium stearate was by far the best anticaking agent compared to the starches (maize, potato, rice, wheat) used for the study. The different starch samples used as anticaking agents prevented caking of Tatale mix to acceptable levels (